Pemikiran A Cornelius Benjamin Tentang Kedudukan Ilmu Kecerdasan Manusia: Tinjauan Filsafat Ilmu: A Cornelius Benjamin's Thoughts on the Position of Human Intelligence: A Review of the Philosophy of Science - Alhail, Hadi (Jurnal Filsafat Indonesia, 2024)
Debates are still going on in rural areas regarding the presence of knowledge of the 3 intelligences Intellectual Quotient (IQ), Emotional Quotion (EQ), and Spiritual Quotion (SQ), because they are considered to have no concrete evidence, because the benchmark for these three intelligences is basically taste. subjective. Qualitative research using library methods. Writing this article applies a literature review to critically review knowledge, ideas or findings contained in literature related to research problems and objectives. Focuses on explaining the nature and existence of the measurement parameters of human intelligence IQ, EQ, and SQ. The analysis technique in this research uses a literature review which is dissected through 4 indicators of philosophy of science, namely: methods, concepts, pre-suppositions and position of science. The research results prove (1) the essence of IQ is figurative ability, verbal ability and numerical ability which are controlled by the work of the left brain; (2) the essence of EQ is self-awareness, self-management, motivation, empathy, and social skills; (3) the essence of SQ is responsibility, humanity and happiness. The three human intelligences IQ, EQ, and SQ are included in the scientific branch of cognitive psychology which discusses human intelligence. SQ is still in theory and cannot be generalized, although research has attempted to formulate SQ measurement indicators, this happens because there is still debate about the god spot as a sign of the existence of SQ in the human brain.